2009
DOI: 10.1007/s00256-008-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal artifact reduction image reconstruction algorithm for CT of implanted metal orthopedic devices: a work in progress

Abstract: The experimental MAR reconstruction algorithm significantly improved CT image quality for patients with large metal implants. However, the MAR algorithm introduced blurring artifact that reduced image quality with small metal implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 13 publications
1
46
2
2
Order By: Relevance
“…2 The maximum width measured on a CT scan for a 7-mm screw is shown. purpose but has been shown to produce significant metal artifact when imaging stainless steel implants, making image interpretation difficult [2,14,17,24,26]. Since volume, or size, of implant adversely affects image quality, surgeons can choose to downsize spinal implants trading fixation strength for improved postoperative imaging capability [26,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The maximum width measured on a CT scan for a 7-mm screw is shown. purpose but has been shown to produce significant metal artifact when imaging stainless steel implants, making image interpretation difficult [2,14,17,24,26]. Since volume, or size, of implant adversely affects image quality, surgeons can choose to downsize spinal implants trading fixation strength for improved postoperative imaging capability [26,31].…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiographs may show gross screw malposition, but advanced imaging is required to truly verify screw position in three dimensions [1]. Numerous authors have reported significant metal artifact when imaging stainless steel implants with CT or MRI making image interpretation difficult [2,14,17,24,26]. The degree of artifact produced is dependent on the cross-sectional area of the implant imaged.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Liu et. al (19) . noted that the MAR reconstruction algorithm improved CT image quality for patients with large metal orthopedic implants, but introduced blurring artifact when used on patients with small metal implants.…”
Section: Discussionmentioning
confidence: 99%
“…A major prerequisite of using fiducial markers for this purpose is clear identification of the markers on the images without introducing a significant amount of artifacts. The reduction of artifacts on the planning CT is especially desirable, since extensive artifacts could interfere with structure delineation and dose calculations, especially if an inhomogeneity correction treatment planning algorithm is used 13 , 19 . Given the plethora of imaging systems available for positioning verification, questions remain about the optimal choice of fiducial marker material for any given imaging system and the effects of various imaging parameters on image quality.…”
Section: Introductionmentioning
confidence: 99%
“…While sufficient for diagnosis, radiographs do not capture the 3D distribution of periprosthetic tissues, where computed tomography (CT) remains the imaging modality of choice [7,8]. Unfortunately, CT suffers from image degradation in the vicinity of metal prostheses [9,10]. Image degradation makes the 3D classification of periprosthetic tissues a difficult taskespecially for low-contrast tissues other than cortical bone.…”
Section: Introductionmentioning
confidence: 99%